Implementation Optimal Location and Sizing of UPFC on Iraqi Power System Grid (132 kV) Using Genetic Algorithm - Ghassan Abdullah Salman; Mohammed Hasan Ali; Ali Najim Abdullah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Electric power systems required efficient processors and intelligent methods for sustainability therefore, in this paper used Flexible AC Transmission System (FACTS) device specifically Unified Power Flow Controller (UPFC) because of its useful properties on series and shunt devices and used Genetic Algorithm (GA) to determine the optimal location and values of UPFC to achieve the following objectives: improve voltages profile, reduce power losses, treatment of power flow in overloaded transmission lines and reduce power generation. Consequently, all of these goals led to a reduction in the total cost of the power system. GA was applied to an Iraqi local power grid system (Diyala 132 kV) to find the optimal values and locations of UPFC for the purpose of achieving the objectives mentioned above using the MATLAB program. The simulation results showed the effectiveness of GA to calculate the optimum values and locations of UPFC and promising results were obtained for the Diyala power network (132 kV) with regard to the desired objectives.